Efektivitas Pembelajaran Tematik Pada Materi Pendidikan Agama Islam (PAI) Di MI Hidayatul Islam Mentoro Tuban - Thoifah, I'anatut (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Learning is a process two-way communication, teaching performed by the teacher, as an educator the students learned performed by a student. It is a model that a many forms, between one to the other to have different characteristics. That can be appropriated with characteritics every student all that is already deeply affect the quality of learning process and the result of the students. This research is to fid out how the thematic and what steps the thematic on a learn in elementary school of MI Hidayatul Islam Mentoro. And this research is able to identify the effectiveness of thematic To get the data needed, researchers use some method is the observation, theinterview, documentation.While for the accumulated data processing using descriptive analysis by researchers.Research shows that models basicallythematic ‘ s learning Islamic Education (PAI) in elementary school of MI Hidayatul Islam Mentoro Tuban.Key world: Effectivity, Learning, Thematic